Trends and pattern of the utilization of cardiovascular medicines in Lithuania in 2003–2012 - Lisauskienė, Ingrida; Garuolienė, Kristina; Gulbinovič, Jolanta (Acta medica Lituanica, 2014)
Background. Despite the wide use of cardiovascular (CV) drugs, CV diseases are still the leading cause of mortality and morbidity. Analysis of drug utilization gives a possibility to evaluate effectiveness of interventions. Materials and methods. The aim of the study was to evaluate CV medicines consumption in Lithuania in 2003–2012. Data was retrieved from the SVEIDRA database of the National Health Insurance Fund. Utilization of the following groups of CVM (ATC group C) was analyzed: C02 – antihypertensive drugs, C03 – diuretics, C07 – beta blocking agents (BBs), C08 – calcium channel blockers (CCBs), C09 – agents acting on the renin–angiotensin system, C10 – lipid modifying agents. ATC/DDD methodology was used. Data was expressed as a number of DDD per 1  000 inhabitants per day (DDD/TID). Results. Consumption of CVM went from 134.5 DDD/TID in 2003 to 352.2 in 2012. Angiotensin converting enzyme inhibitors (ACEI) were the most consumed ones (66–114.8 DDD/TID), followed by CCBs (19.4–38.8 DDD/TID) and BBs (12.5–52.6 DDD/TID).There was high consumption of antihypertensives (4.7–23.9 DDD) and low consumption of diuretics (9.4–16.9 DDD/TID) and lipid modyfing agents (0.4–7.4 DDD/TID). Increasing utilization was noticed in the angiotensin II antagonist (ARBs) group (42 DDD/TID), ACEI combinations (38.6 DDD/TID) and ARBs combinations (12.9 DDD/TID) in 2012. Conclusions. Utilization of CV medicines increased in Lithuania in 2003–2012. ACEI held the first position. An extremely low utilization of lipid modifying agents, diuretics and high consumption of alpha-receptor blockers showed the need of actions on changing the prescribing pattern of CV drugs.
Keywords: drug utilization (trends); cardiovascular medicines; hypertension medication; Lithuania